Papel da migração celular e de mediadores inflamatórios na infecção experimental por Leishmania sp - Wakimoto, Dayanne Tozatto (2009)
American Cutaneous Leishmaniasis (ACL), a disease caused by protozoa of the genus Leishmania, is endemic in Brazil and the State of Paraná. The ACL is a disease that mainly concern by the development of crippling injuries in the nasal mucosa, oral cavity and pharynx. Once inside the macrophage antigens processed and presented to T cells, depending on the species of Leishmania and host susceptibility, require a response from Th1 or Th2, resulting in the production of certain cytokines. The objective of this study was investigate in vivo, after inoculation of Leishmania (Leishmania) amazonensis and Leishmania (Viannia) braziliensis in BALB/c mice, the involvement of immunomodulators in the recruitment of leukocytes and establish a relationship between cell migration and production of mediators inflammatory front infection by two distinct species of Leishmania sp. It was observed that infection caused by L. (L.) amazonensis stimulated more the migration of cells in relation to infection by L. (V.) braziliensis, with a predominance of neutrophils followed by macrophages in the groups infected with L. (L.) amazonensis, and eosinophils in the groups infected with L. (V.) braziliensis. Furthermore, it was found that after inoculation of L. (L.) amazonensis PGE2 interfered significantly with the levels of nitric oxide TNF-α and IL-12. We found that PGE2 possibly served as an important regulator of immune response in the initial phase of Leishmania infection, inducing the production of nitric oxide and IL-12 and negatively regulates cell migration, a process whose mechanism may be linked to the production of TNF-α.